2009
DOI: 10.3945/ajcn.2008.27281
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of protein quality on postprandial lipemia in response to a fat-rich meal in type 2 diabetes: comparison of whey, casein, gluten, and cod protein

Abstract: Background: Enhanced and prolonged postprandial triglyceride responses involve increased cardiovascular disease risk in type 2 diabetes. Dietary fat and carbohydrates profoundly influence postprandial hypertriglyceridemia, whereas little information exists on the effect of proteins. Objective: The objective was to compare the effects of the proteins casein, whey, cod, and gluten on postprandial lipid and incretin responses to a high-fat meal in persons with type 2 diabetes. Design: A crossover study was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
109
4
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(122 citation statements)
references
References 51 publications
(57 reference statements)
5
109
4
4
Order By: Relevance
“…14 However, when whey protein, another milk protein, was added to a fat-rich meal it acutely reduces the postprandial triglyceride response in T2DM subjects compared with casein, cod and gluten. 16 Pal et al 17 has confirmed the improvement in PPL after ingestion of whey protein in overweight postmenopausal women.…”
Section: Introductionmentioning
confidence: 58%
“…14 However, when whey protein, another milk protein, was added to a fat-rich meal it acutely reduces the postprandial triglyceride response in T2DM subjects compared with casein, cod and gluten. 16 Pal et al 17 has confirmed the improvement in PPL after ingestion of whey protein in overweight postmenopausal women.…”
Section: Introductionmentioning
confidence: 58%
“…We excluded the possibility that increments in insulin concentration after these mixed meals had suppressed the levels of the biomarkers by finding no correlation between the changes in plasma insulin concentration and any biomarkers (data not shown). The protein intake with the butter and the cream meals was substantially less than with the cheese and yoghurt meals (Tables 2a and 2b) that may be relevant since Mortensen et al (2009) reported that different sources of protein added to a high-fat meal elicited different triglyceridemic and glycemic responses. Our priority was to minimize the differences in dairy fat and in energy content.…”
Section: Discussionmentioning
confidence: 99%
“…Milk proteins have been extensively investigated for their insulinotropic and glucose-lowering effects in healthy subjects (73,75,82,83,(90)(91)(92)(93)(94)(95)(96)(97)(98)(99) and to a limited extent in individuals with suboptimal glucose control (100)(101)(102)(103)(104)(105)(106) . The dose varied significantly between studies from as little as 10 g (92,105,106) -51 g (91) .…”
Section: Short-term Studies On Glycaemic Controlmentioning
confidence: 99%